Hubungan Peran Keluarga Sebagai Predisposing Factor dengan Kepatuhan Penderita Tuberkulosis Paru di Puskesmas Bromo Tahun 2023 - Balqis Nurmauli Damanik; Theresia Sarywaty Situmorang (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Tuberculosis (TB) is an infectious disease caused by the bacillus mycobacterium tuberculosis. Non-compliance with medication regimen is a global problem, because if you do not follow the course of treatment correctly it can cause drug resistance, recurrence of the disease, and even death. The aim of this research is to analyze the relationship between the role of the family as a reinforcing (predisposing) factor and the behavior of TB sufferers at the Bromo Community Health Center, Medan Denai District in 2023. This type of research is cross sectional. The sampling technique is purposive sampling. The total sample was 80 PMOs who were families of TB sufferers. The instrument used was a questionnaire sheet. The results of this study show that there is a relationship between family history and compliance with pulmonary TB sufferers by carrying out the Chi-Square test with a p value < 0.05, namely p < 0.001 with a confidence level of 95%. With these results, it is recommended that families continue to provide maximum family support in order to improve the condition of pulmonary TB sufferers so that patients can undergo treatment regularly.